2008
DOI: 10.2174/092986608785849245
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Structural Investigations of Bothropstoxin-II, a Myotoxic Asp49 Phospholipase A2 from Bothrops jararacussu Venom

Abstract: Bothropstoxin-II a calcium-dependent enzyme from Bothrops jararacussu venom causes tissue damage and several haemostatic disorders including platelet aggregation. In order to elucidate the structural determinants of its multiple pharmacological activities, we have studied the effects of suramin on Bothropstoxin-II and present details concerning the mode of binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This interaction was demonstrated on the fucCS affinity column and in the electrophoresis experiments, which confirmed that a negatively charged substance combined with the toxins. The charge interaction model is supported by the observation that BthTx-II, in the same dose of BthTx-I, did not cause significant muscle damage, and it has been described that BthTx-II is only weakly positively charged, while BthTx-I display strong positive charge (Murakami et al, 2008). Perfusion with both toxins together induced more extensive muscle damage, which agrees with previous data showing that, in myotubes, Asp49 and Lys49 myotoxins act synergistically to increase the plasma membrane Ca 2þ permeability, and consequently cell death (Cintrafrancischinelli et al, 2009(Cintrafrancischinelli et al, , 2010, which has recently been observed in vivo by Mora-Obando et al (2014), who demonstrated a clear enhancement of myonecrosis by the combined action of these two kinds of toxins in mice.…”
Section: Discussionmentioning
confidence: 82%
“…This interaction was demonstrated on the fucCS affinity column and in the electrophoresis experiments, which confirmed that a negatively charged substance combined with the toxins. The charge interaction model is supported by the observation that BthTx-II, in the same dose of BthTx-I, did not cause significant muscle damage, and it has been described that BthTx-II is only weakly positively charged, while BthTx-I display strong positive charge (Murakami et al, 2008). Perfusion with both toxins together induced more extensive muscle damage, which agrees with previous data showing that, in myotubes, Asp49 and Lys49 myotoxins act synergistically to increase the plasma membrane Ca 2þ permeability, and consequently cell death (Cintrafrancischinelli et al, 2009(Cintrafrancischinelli et al, , 2010, which has recently been observed in vivo by Mora-Obando et al (2014), who demonstrated a clear enhancement of myonecrosis by the combined action of these two kinds of toxins in mice.…”
Section: Discussionmentioning
confidence: 82%
“…The residues Gly28, Gly29, Arg32 and Gly33 are involved in the coordination of Ca 2+ ion in Asp49-PLA 2 s [35][36][37][38], which plays a role in the stabilization of the tetrahedral intermediate during catalysis. In Lys49-PLA 2 homologues, the Lys49-NZ atom is located at the position of the Ca 2+ ion and is coordinated by the backbone atoms from the CGVG/LGR motif.…”
Section: Lys49 Coordination and Its Role In The Stabilization Of Tetrmentioning
confidence: 99%
“…PAV may prevent death, but does not prevent local tissue damage and subsequent functional disabilities (17). Researchers have been seeking alternative treatments that could antagonize such local effects, increasing tissue recovery and hastening the patient's return to daily routine (18-23). …”
Section: Introductionmentioning
confidence: 99%